UML Design of Business Intelligence System for Small-Scale Enterprises - Esiefarienrhe, Bukohwo Michael; Moemi, Thusoyaone Joseph (Universitas Bina Darma, 2024)
Small scale enterprises (SSEs) face numerous challenges in managing and processing their business data, which often leads to inefficiencies, errors, and suboptimal decision-making. To address these challenges, the design of a Business Intelligence (BI) system for SSEs using Unified Modeling Language (UML) diagrams is proposed. UML diagrams provide a visual modeling language that facilitates the design, analysis, and implementation of complex systems. The proposed BI system is designed to enable SSEs to gather, integrate, analyze, and present data from various sources, including sales, finance, operations, and customer relations. The agile methodology was used in the design of the mobile intelligence system (MoIS) utilizing the Scrum method because of its time-boxed iterations (sprints), cross-functional team collaboration, and regular feedback loops. The UML diagrams used in this design are use case diagrams, activity diagrams, class diagrams, and sequence diagrams. The use case diagrams identify the system's users and their interactions with the system, while the activity diagrams describe the system's processes and workflows. The class diagrams depict the system's data structures and relationships, and the sequence diagrams specify the interactions between system components. The proposed BI system provides SSEs with the necessary tools to make informed decisions, improve operational efficiency, and gain a competitive advantage. The UML-based design approach ensures that the BI system is well-structured, easy to maintain, and scalable. The effectiveness of the proposed BI system is demonstrated through a case study of an SSE in the retail industry. The results indicate that the BI system improves the SSE's decision-making processes and enables it to respond more quickly to changing market conditions. The proposed BI system using UML diagrams is a valuable contribution to the field of BI systems design and is expected to benefit SSEs in various industries.